2009
DOI: 10.1038/nsmb.1641
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mre11 in chromosomal nonhomologous end joining in mammalian cells

Abstract: Here we have used an intrachromosomal substrate to monitor the end joining of distant ends, which leads to DNA rearrangements in mammalian cells. We show that silencing Mre11 reduces the efficiency of nonhomologous end joining (NHEJ), affecting both the canonical and alternative pathways, partly in a manner that is independent of the ataxia-telangiectasia mutated kinase (ATM). Silencing of Rad50 or CtIP decreases end-joining efficiency in the same pathway as Mre11. In cells defective for Xrcc4, the MRE11-RAD50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
305
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(323 citation statements)
references
References 60 publications
16
305
1
Order By: Relevance
“…To this end, we utilized cell lines that contain stably integrated reporters to assess the rates of HR (DR-GFP 10,11 ) and NHEJ. 12 --14 For NHEJ, we used cell lines containing two types of NHEJ-reporter substrates; the pCOH-CD4 that permits analysis of the NHEJ of two distal ends (separated by 3.2 kb), 12,13 and a GFP-based substrate, 14 to measure the NHEJ on closely adjacent ends, separated by only 34 bp. 14 Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we utilized cell lines that contain stably integrated reporters to assess the rates of HR (DR-GFP 10,11 ) and NHEJ. 12 --14 For NHEJ, we used cell lines containing two types of NHEJ-reporter substrates; the pCOH-CD4 that permits analysis of the NHEJ of two distal ends (separated by 3.2 kb), 12,13 and a GFP-based substrate, 14 to measure the NHEJ on closely adjacent ends, separated by only 34 bp. 14 Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…and CtIP, are involved in MMEJ [25][26][27][28]. Indeed, Zhang and Jasin reported that CtIP depletion decreases translocation frequency both in wild-type and KU70(-/-) murine ES cells [29].…”
Section: Atm Suppresses Dicentric Frequency In the Same Pathway As Dnmentioning
confidence: 99%
“…The MRN complex is also thought to participate in ATR-CHK1 kinase activation by facilitating DNA end resection [14][15][16][17][18]. It participates in multiple downstream pathways for checkpoint signaling, DNA replication, telomere maintenance, nonhomologous end joining and meiotic recombination [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%